2013
DOI: 10.1210/en.2012-1953
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the Adrenal Gland in the Spiny Mouse, With Particular Reference to Production of the Steroids Cortisol and Dehydroepiandrosterone

Abstract: Synthesis of the androgen dehydroepiandrosterone (DHEA) by the fetal adrenal gland is important for placental estrogen production and may also be important for modulating the effects of glucocorticoids on the developing brain. The presence of cortisol in spiny mouse (Acomys cahirinus) blood led us to determine whether the adrenal gland of this precocial rodent also synthesized DHEA. Cytochrome P450 enzyme 17α-hydroxylase/17,20-lyase (P450c17), cytochrome-b5 (Cytb5), and 3β-hydroxysteroid dehydrogenase (3βHSD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 54 publications
1
58
0
1
Order By: Relevance
“…In rats and Balb/c mice, the cytochrome P450c17 is absent in adrenal and therefore the authors suggest that this organ does not contribute to production of androgens (van-Weerden et al, 1992). However, in C. porcellus, the cytochrome P450c17 enzyme is predominantly distributed in the fasciculate zone, but is also found in lower quantities in the reticular zone (Shinzawa et al, 1988), as also found in Spiny mouse (Quinn et al, 2013). In the absence of P450c17 in the glomerular zone C21-deoxy-steroids are produced, leading to mineralocorticoids aldosterone.…”
Section: ) and Myocastor Coypusmentioning
confidence: 85%
See 3 more Smart Citations
“…In rats and Balb/c mice, the cytochrome P450c17 is absent in adrenal and therefore the authors suggest that this organ does not contribute to production of androgens (van-Weerden et al, 1992). However, in C. porcellus, the cytochrome P450c17 enzyme is predominantly distributed in the fasciculate zone, but is also found in lower quantities in the reticular zone (Shinzawa et al, 1988), as also found in Spiny mouse (Quinn et al, 2013). In the absence of P450c17 in the glomerular zone C21-deoxy-steroids are produced, leading to mineralocorticoids aldosterone.…”
Section: ) and Myocastor Coypusmentioning
confidence: 85%
“…Each part of adrenal gland has different cell types: cells producing sexual steroid hormones, glucocorticoids and mineralocorticoids are present in the cortex, and chromaffin cells, which are producers of catecholamine and neuropeptides are present in medullar region (Hîncu et al, 2006;Kempná and Flück, 2008;Chang et al, 2011;Parker et al, 2011;Quinn et al, 2013;Qiu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because rats and mice lack postnatal expression of CYP17 in the adrenal, they have long been considered as nonrelevant experimental models to study adrenarche. However, the spiny mouse has been shown to express CYP17 and to produce adrenal-derived androgens from an individualized zR (47)(48)(49). This provides cues for possible usefulness of rodent models to explore underpinnings of adrenarche.…”
Section: Discussionmentioning
confidence: 99%